SISTEM INFORMASI DATA KREDIT KONSUMEN REPEAT ORDER PADA PT ADIRA QUANTUM MULTIFINANCE BENGKULU - Khairil, Khairil; sono, Aji Sudar (Jurnal Media Infotama, 2011)
In today‟s era of reform information technology is a technology that is widely used to support the work so much caster to be implemented with the achievement of a satisfactory, for example Borland Delphi 7 program that using in PT Adira Quantum Multifinance Bengkulu.This study aims to simplify and accelerate the process of information is needed and can generate data or reports are accurate.Issues to be discussed in this study is “How to create a system of costomer credit data information Repeat Order PT Adira Quantum Multifinance Bengkulu using Delphi 7 language?”. By making the Borland Delphi 7 program is then ablepetrified in search of repeat orders yag costumer data needed PT Adira Quatum Multifinance Bengkulu